The Role of Endoscopic Retrograde Cholangiopancreatography in the Management of Biliary Complication Post-Laparoscopic Cholecystectomy - Akool, Mohamed Abdzaid; Al-Hakkak, Samer Makki Mohamed; Al-Wadees, Alaa Abood (Open Access Macedonian Journal of Medical Sciences, 2021)
BACKGROUND: Laparoscopic cholecystectomy considers a golden surgery for gallbladder removal nowadays, and it carries some complications like biliary injuries, which can manage successfully by endoscopic retrograde cholangiopancreatography. AIM: To estimate the role of endoscopic management of bile duct injury (BDI) following laparoscopic cholecystectomy. PATIENT AND METHODS: A prospective study conducted at Al-Sader Medical City, Najaf City, Iraq, during the period between September 2018 and December 2020, included 44 patients complicated by the biliary injury resulting in a persistent biliary leak and/or jaundice after laparoscopic cholecystectomy and evaluated by endoscopic retrograde cholangiopancreatography (ERCP). RESULTS: Findings revealed that 25% of cases had complete BDI, only one managed by plastic stent placement, the other 10 referred for open surgical constructions, 61% had partial injury associated with the biliary leak, all managed by sphincterotomy and plastic stent placement through ERCP, almost 7% had a partial clipping of bile duct all managed with sphincterotomy, balloon dilatation/stone extraction, and plastic stent placement, 5% had slipped clips of cystic duct stump, are managed with sphincterotomy and plastic stent placement. Moreover, only one patient, 2%, had distal common bile duct stone with bile leak, managed by sphincterotomy and stone extraction. CONCLUSIONS: Laparoscopic cholecystectomy, a gold standard therapeutic option for symptomatic cholecystolithiasis, is associated with an increased risk of biliary injury due to many factors. ERCP is a safe means of diagnosing the cause of bile leakage after laparoscopic cholecystectomy. It also offers definitive treatment in most cases by endoscopic sphincterotomy and plastic stent placement.